2016
DOI: 10.17987/icfj.v8i0.283
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Disease has no Negative Impact on Educational Achievements and Employment among Maltese Adult Patients under Clinical Follow-Up

Abstract: <p><strong>Background:</strong> Most children born with congenital heart disease (CHD) nowadays survive into adulthood.  The aim of this study was to investigate the potential impact of CHD on educational achievements and employment in Maltese adult patients.</p><p><strong>Methods:</strong> A bespoke self-reporting questionnaire based on the 2008 European Health Interview Survey (EHIS 2008) was distributed to 162 consecutive Maltese adult congenital heart disease (ACHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, in contrast to previous guidelines, 6 education and employment are no longer mentioned in the latest European guidelines for the management of grown-up CHD. [14][15][16] Research in other chronic diseases (eg, rheumatoid arthritis, asthma, chronic obstructive pulmonary disease, diabetes mellitus, and ischemic heart disease) has consistently shown that employment and work ability are negatively influenced by these conditions. [8][9][10][11][12][13] In contrast, studies from Finland, Sweden, and Malta, have reported employment rates similar or even above those of the general population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in contrast to previous guidelines, 6 education and employment are no longer mentioned in the latest European guidelines for the management of grown-up CHD. [14][15][16] Research in other chronic diseases (eg, rheumatoid arthritis, asthma, chronic obstructive pulmonary disease, diabetes mellitus, and ischemic heart disease) has consistently shown that employment and work ability are negatively influenced by these conditions. [8][9][10][11][12][13] In contrast, studies from Finland, Sweden, and Malta, have reported employment rates similar or even above those of the general population.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] In contrast, studies from Finland, Sweden, and Malta, have reported employment rates similar or even above those of the general population. [14][15][16] Research in other chronic diseases (eg, rheumatoid arthritis, asthma, chronic obstructive pulmonary disease, diabetes mellitus, and ischemic heart disease) has consistently shown that employment and work ability are negatively influenced by these conditions. Patients with other chronic diseases are less often employed, work fewer hours when they work and report limitations at work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the included studies is presented in Table 1. The association of CHD with educational attainment was the main aim for 14 (33% of total) studies (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), while in the remaining 28 (67% of total) studies (35-62) it was not. For most of those, information on education attainment was extracted from tables describing study population characteristics.…”
Section: Resultsmentioning
confidence: 99%